ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN SAAT PANDEMI COVID-19 PADA PT TELEKOMUNIKASI INDONESIA TBK - Khairunnisa; Siregar, Lukman Hakim; Rozi, Fachrul (Jurnal Manajemen Akuntansi dan Ilmu Ekonomi, 2024)
This study aims to find out the differences in financial performance of PT. Telekommunikasi Indonesia Tbk Company before and during the COVID-19 pandemic period 2019–2021, as seen from the ratios of liquidity, profitability, solvency, and activity. This study uses a type of descriptive research with a quantitative approach. The results of this study are seen in several ratios, with the results of the ratio of provability and also liability showing that the performance of Telecom Indonesia Tbk has had a positive impact since the time of the COVID-19 pandemic in 2020 and 2021 compared to the pre-COVID-19 period, which showed smaller corporate liability compared with its assets and equity. In the profitability section, namely ROA (return on assets), ROE (return on equity), and NPM (net profit margin), it can be concluded that the COVID-19 pandemic had a positive impact on the financial performance of PT Telecommunication Indonesia Tbk. Because of the four increasing ratios with the low operating burden on the liquidity side, namely the current ratio and the net working capital to asset ratio, it can be concluded that the actual ratio of PT Telecommunikasi Indonesia Tbk has increased. On the NWCA side, liquidity decreased due to the impact of COVID-19 compared to before the COVID-19 pandemic.